2017
DOI: 10.1002/anie.201706894
|View full text |Cite
|
Sign up to set email alerts
|

Electro‐kinetic Separation of Rare Earth Elements Using a Redox‐Active Ligand

Abstract: Purification of rare earth elements is challenging due to their chemical similarities. All of the deployed separation methods rely on thermodynamic properties, such as distribution equilibria in solvent extraction. Rare-earth-metal separations based on kinetic differences have not been examined. Herein, we demonstrate a new approach for rare-earth-element separations by exploiting differences in the oxidation rates within a series of rare earth compounds containing the redox-active ligand [{2-(tBuN(O))C H CH }… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 23 publications
0
42
0
2
Order By: Relevance
“…Since this strategy has the potential to be modular and applicable to a variety of established separations methods, we also incorporated a magnetic field into our previously reported electrokinetic separations (Table ,) which used the rate differences in a chemical oxidation process to partition two isostructural rare earth complexes . While almost no change was observed in the EF solid values when this modified electrokinetic method is performed in the presence of a magnetic field, the EF filtrate value nearly doubled, giving a larger SF Eu:Dy value when this separation was performed in the presence of a magnetic field (Table , entry 2).…”
Section: Resultsmentioning
confidence: 99%
“…Since this strategy has the potential to be modular and applicable to a variety of established separations methods, we also incorporated a magnetic field into our previously reported electrokinetic separations (Table ,) which used the rate differences in a chemical oxidation process to partition two isostructural rare earth complexes . While almost no change was observed in the EF solid values when this modified electrokinetic method is performed in the presence of a magnetic field, the EF filtrate value nearly doubled, giving a larger SF Eu:Dy value when this separation was performed in the presence of a magnetic field (Table , entry 2).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent vacuum distillation at 1000°C afforded the more volatile NdCl 3 with a separation factor estimated at 570, an impressive value for nearly adjacent REs (59). The above methods have focused on the RE redox chemistry; however, our group has demonstrated that the increasing Lewis acidity of the REs can affect the irreversible oxidative electron transfer rate of a coordinated redox-active ligand (60). In this case, the selectively oxidized complexes were separated by filtration.…”
Section: Redox Methodsmentioning
confidence: 99%
“…This result is in agreement with our observations on related hydroxylamine ligands for the lanthanide series where a similar correlation was drawn and which allowed for the design of a separation system based on these small differences of oxidation potentials and rates caused by the increasing Lewis acidity of the central cations. 35 A second oxidation event can be observed and is attributed to the subsequent ligand-based oxidation of the hydroxylamine ligand to its oxoammonium form (NO • /N=O + ) at higher potential. 20,36 On the reductive side of the CV of 2, small ligand-based return reduction events were observed, in analogy with the processes observed for the Th complex.…”
Section: (B) L 3 -Edge X-ray Absorption Spectroscopy (Xasmentioning
confidence: 99%